Baseline prevalence and type distribution of human papillomavirus in healthy Chinese women aged 18–25 years enrolled in a clinical trial. Issue 11 (20th May 2014) - Zhao, Fang‐Hui; Zhu, Feng‐Cai; Chen, Wen; Li, Juan; Hu, Yue‐Mei; Hong, Ying; Zhang, Yi‐Ju; Pan, Qin‐Jing; Zhu, Jia‐Hong; Zhang, Xun; Chen, Yong; Tang, Haiwen; et al.
Abstract : Baseline human papillomavirus (HPV) prevalence and type distribution were evaluated in young Chinese women enrolled in a clinical trial of an HPV vaccine (ClinicalTrials.gov registration NCT00779766). Cervical specimens and blood samples were collected at baseline from women aged 18–25 years ( n  = 6, 051) from four sites across Jiangsu province. Cervical specimens were tested for HPV DNA by SPF10 PCR‐DEIA‐LiPA25 version 1, and HPV‐16/18 type‐specific polymerase chain reaction. Anti‐HPV‐16 and anti‐HPV‐18 antibody titres were quantified by enzyme‐linked immunosorbent assay. At baseline, 15.3% of women were DNA positive for any of 14 HPV high‐risk (hr) types (HPV‐16/18/31/33/35/39/45/51/52/56/58/59/66/68). The most commonly detected hrHPV types in cervical specimens were HPV‐52 (4.0%) and HPV‐16 (3.7%). High‐risk HPV DNA‐positivity increased with severity of cytological abnormalities: 39.3% in atypical squamous cells of undetermined significance, 85.0% in low‐grade squamous intraepithelial lesions and 97.8% in high‐grade squamous intraepithelial lesions (HSIL). The hrHPV types most frequently detected in HSIL were HPV‐16 (63.0%), HPV‐18 (17.4%), HPV‐52 (17.4%), HPV‐58 (15.2%) and HPV‐33 (15.2%). The hrHPV types most frequently detected in cervical intraepithelial neoplasia 2+ were HPV‐16 (66.1%), HPV‐33 (16.1%), HPV‐52 (16.1%), HPV‐58 (14.5%) and HPV‐51 (11.3%). Multiple hrHPV infections were reported for 24.4% of hrHPV DNA positive women. Regardless of baseline HPV DNA status, 30.5% and 16.0% of subjects were initially seropositive for anti‐HPV‐16 and anti‐HPV‐18, respectively. In conclusion, the high baseline seropositivity rate and intermediate prevalence of cervical hrHPV types in Chinese women aged 18–25 years underlines the importance of early HPV vaccination in this population. Abstract : What's new? In China, cervical cancer is the second most frequent cancer among women aged 15–44 years. The authors collected baseline data on prevalence and type distribution of human papillomavirus (HPV) from more than 6, 000 healthy Chinese women aged 18–25 years participating in a large vaccine efficacy trial. Regardless of cytology, 15.3% of women were positive for high‐risk HPV types, with HPV‐52 (4.0%), HPV‐16 (3.7%), HPV‐51 (1.7%) and HPV‐58 (1.5%) being the most frequently detected. This high baseline prevalence of high‐risk HPV types underscores the importance of early vaccination among Chinese women.